2019
DOI: 10.1094/pdis-01-19-0199-re
|View full text |Cite
|
Sign up to set email alerts
|

Field Infection of Virus-Free Sugarcane by Sugarcane Yellow Leaf Virus and Effect of Yellow Leaf on Sugarcane Grown on Organic and on Mineral Soils in Florida

Abstract: Sugarcane yellow leaf virus (SCYLV), the causal agent of yellow leaf, is widespread in Florida. Two field trials were set up, one on organic soil and one on mineral soil, to investigate the rate and timing of sugarcane infection by SCYLV under field conditions and the effect of the virus on yield. Each trial consisted of plots planted with healthy or SCYLV-infected seed cane of two commercial cultivars. Virus prevalence varied from 83 to 100% in plots planted with infected seed cane regardless of cultivar, loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Up to 14% loss in sugar yield was described in Louisiana (Gonçalves et al, 2005;Grisham et al, 2009). In Florida, 11% loss was recorded in sugar yield and stalk weight (Comstock and Miller, 2004), 14% loss in sugar yield (Flynn et al, 2005) and 11% to 27% in sugarcane yield were reported in different experimental fields (Boukari et al, 2019). In Reunion of Island, 11% and 28% losses were documented in sugar content and stalk weight, respectively due to virus infection (Rassaby et al, 2004).…”
Section: Economic Impact Of Scylvmentioning
confidence: 99%
“…Up to 14% loss in sugar yield was described in Louisiana (Gonçalves et al, 2005;Grisham et al, 2009). In Florida, 11% loss was recorded in sugar yield and stalk weight (Comstock and Miller, 2004), 14% loss in sugar yield (Flynn et al, 2005) and 11% to 27% in sugarcane yield were reported in different experimental fields (Boukari et al, 2019). In Reunion of Island, 11% and 28% losses were documented in sugar content and stalk weight, respectively due to virus infection (Rassaby et al, 2004).…”
Section: Economic Impact Of Scylvmentioning
confidence: 99%
“…The expression of SCYL symptoms is complex and usually occurs in late stages of plant development, being mainly characterized by the intense yellowing of midribs in the abaxial surface of leaves 11 , 12 . SCYLV alters the metabolism and transport of sucrose and photosynthetic efficiency 13 , 14 , impairing plant development, which eventually reflects in productivity losses 15 20 . Many SCYL symptoms may, however, be caused by other stresses or plant senescence 12 , 15 , 21 , making SCYL identification troublesome.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf yellowing is the characteristic symptom of ScYLV infection, starting from the midrib of the abaxial leaf surface and, in advanced stages, spreading through the leaf blade, while the midrib of the adaxial surface presents a reddish color [ 3 ], shortening of the stalks’ internodes [ 4 ] and accumulation of sucrose in the phloem [ 5 ]. The virus has become endemic in the main producing countries [ 6 ] and remains a major concern for sugarcane producers [ 7 ], causing field losses of 20 to 60% in susceptible cultivars [ 8 , 9 , 10 ], and of up to 14% in sugar net yield [ 11 ].…”
Section: Introductionmentioning
confidence: 99%